Comparative analysis of the biomechanical behavior of anterograde/retrograde nailing in supracondylar femoral fractures. (April 2020) - Herrera, A.; Albareda, J.; Gabarre, S.; Ibarz, E.; Puértolas, S.; Mateo, J.; Gracia, L.
Highlights: Surgical treatment of supracondylar femoral fractures is controversial, with different surgical options. Intramedullary nailing has emerged as a new surgical technique in the treatment of that type of fractures. A comparative study simulating the biomechanical behavior of anterograde and retorgrade nail is performed. Anterograde nailing is an excellent indication in supracondylar fractures of femur type A. Anterograde nailing present clear benefits compared to retrograde nailing in the treatment of fractures of femur type A. Abstract: Supracondylar femoral fractures account for a noticeable percentage of the femoral shaft fractures, affecting two etiological groups: high energy trauma in young men, with good bone quality, and older women with osteoporotic femur. Surgical treatment of those kind of fractures remains controversial, with different surgical options such as plate and sliding barrel locking condylar plate, less invasive stabilization system (LISS) or intramedullary nailing, which has emerged as a new fixation choice in the treatment of that type of fractures. The present work performs a comparative study about the biomechanical behavior of anterograde and retrograde nailing in supracondylar femoral fractures type A, in order to determine the best choice of nailing and locking configuration. A three-dimensional finite element model of the femur was developed, modeling femoral supracondylar fracture and different nailing configurations, both for anterograde and retrograde nails. The study was focused on the immediately post-operative stage, verifying the appropriate stability of the osteosynthesis. The obtained results show a better biomechanical behavior for anterograde nails, providing a better stability from the point of view of global movements, lower stresses in screws, and less stress concentration in cortical bone. So, for the analyzed fractures and osteosyntheses types, anterograde nailing has demonstrated to be a better surgical option, being an excellent indication in supracondylar fractures of femur, with clear benefits compared to retrograde nailing, providing a better stabilization which enables for a more satisfactory fracture healing.